River-Adjacent Buildings: Unraveling Soil-Structure Interaction Challenges and Engineering Triumphs through Case Studies - Gaye, Daouda; Hassan Mohamed, Hassan Omer; Serigne Saliou, Sene (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
This study presents a comprehensive analysis of four prominent river-adjacent building projects: Riverside Tower in London, Marina Bay Sands in Singapore, Burj Khalifa in Dubai, and One World Trade Center in New York. By delving into the geological conditions, design strategies, construction hurdles, and performance evaluations of each, the research unravels the complex soil-structure interaction (SSI) challenges these structures faced. Through advanced mathematical models and real-time monitoring, the study demonstrates how innovative engineering solutions, such as piled and raft foundations, waterproofing techniques, and seismic design considerations, were implemented to overcome SSI-induced settlement, flood risks, and dynamic loading impacts. The findings offer invaluable insights and practical guidelines for future river-adjacent building projects, ensuring enhanced structural integrity and long-term performance in such challenging environments.